Tree - Lingual : Media Aplikatif untuk Mengajar Trilingual di TK/TPA Al Mu’minun, Samarinda, Kalimantan Timur - Rizky Sulvika Puspa Rinda; Ditha Nizaora; Noorma Kurnyawaty (Penerbit Goodwood, 2023)
Purpose: The aim of this Community Service was to train the participants, whom the teachers of TK/TPA Al Mu’minun, to use the Tree – Lingual teaching media or the Language Tree as well as to facilitate them exploring their skills in developing teaching aids. Research methodology: The method used was training the participants, both teachers and students of the TK/TPA Al Mu’minun using tree – lingual teaching media which the students were able to learn three languages ??at once, namely Indonesian, English, and Arabic by using the trilingual cards which were put inside the character pouches where were attached in the branches and trunks of the Language Tree. Results: From the training activities showed that the students enthusiastically engaged to the training session, especially when they were asked to come in front of the class to choose the pouches on the tree – lingual. The teachers were also excited to practice on how to use the learning media as well as disclosed that they had several ideas on developing the learning media. Conclusions: Through this training, the teachers were also provided with the knowledge about how to create and develop learning media that are not only applicable and innovative, but also brings fun for students. They were also expected to be able to increase productivity in creating educational products to improve the trilingual learning process in their area. Limitations: This Community Service was limited to the use of tree - lingual teaching media for primary level. Contribution: This learning media can be applied in language classed for primary or secondary level.